3PL: experiences from China resources logistics (Hong Kong). Issue 1 (15th November 2004) - Gunasekaran, A.; Ngai, E.W.T.
In this paper, a case study of logistics information systems is presented. Logistics has been playing a tremendous role in providing a competitive advantage for companies in a networked economy and market. In the past ten years, companies have been successful in reducing lead-time along the upstream stages of the supply chain. Since the emergence of a global market and the resulting intensified competitiveness, downstream logistics has gained prominence in ensuring that the goods manufactured are delivered to customers at the right time with minimum transportation costs. Also, companies outsource their logistics services because of the complexity of the logistics operations and to reduce the time needed for their product to reach the market. This has provided opportunities for many 3PL-service companies to flourish. Considering the importance of downstream logistics in the networked economy of the twenty-first century, a case study conducted at CRC Logistics (Hong Kong) is presented to highlight the strategies, methods and technologies needed to improve the performance of logistics operations. The case analysis provides a framework of how logistics operations are performed in the industry. Some of the critical success factors that have been identified for effective 3PL management are also presented.